Genome-Wide Identification and Expression Analysis of the GRF and GIF Gene Families in Prunus avium - Hongxu Chen; Yangang Pei; Wanjia Tang; Hongfen Li; Yidi Huang; Yizhe Chu; Guanqiong Kou; Wenyi Niu; Runmei He; Ronggao Gong (Agronomy)
Prunus avium is a woody plant of economic importance within the genus Prunus, the family Rosaceae, which is affected by various environmental factors during its long growth period. Growth-regulating factors (GRFs) and GRF-interacting factors (GIFs) are essential in regulating plant growth and development, responding to environmental stresses, and responding to exogenous hormone induction. Genome-wide analysis showed 13 GRF genes on eight chromosomes and three GIF genes on three chromosomes in P. avium, clustered into three and two branches, respectively. Cis-acting element analysis indicated that the PavGRF promoters contained regulatory elements associated with hormones, light stress, and growth development. Therefore, we evaluated the effects of gibberellin and light stress on the GRF and GIF genes in P. avium at different stages. Transcriptome data revealed that five PavGRFs exhibited elevated expression levels during the green ripening and color conversion stages in P. avium, PavGRF9 and PavGIF1 displayed higher expression during the full red stage, and gibberellin treatment led to the upregulation of these five PavGRFs and PavGIF1 during the full red stage. However, light stress did not significantly impact the expression of PavGRFs and PavGIFs. Additionally, miR396 could bind to the PavGRFs, thereby regulating the expression level of PavGIF after transcription. This study revealed the potential roles of the GRF and GIF transcription factor families in P. avium fruit growth and development, exogenous hormone treatment, and light stress, laying the foundation for further research on the roles of the GRF and GIF gene families in P. avium.